Reflexões sobre a Prática Educativo-Crítica, Gestão Social e Educação a Distância: o caso do PNAP em Santa Catarina - Carlos Eduardo Justen (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2012)
This article analyzes the experience of a thematic seminar on Social Management offered in 2011, by the curricular structure of the course of Bachelor of Public Administration, distance mode, in six poles at Federal Universit of the State of Santa Catarina (UFSC), seeking characterize the concept of education developed and professional training can result. From the case study, qualitative and descriptive orientation were investigated four analytical categories ¿ deliberative citizenship, vocational and epistemic dimensions of the political pedagogical, and conceptual clarity and analytical capacity on Social Management. The results showed an orientation to the strategic approach to education in public administration, where they repeat the ills of classroom teaching, increasing the risk of mass cognitive through a technological rationality that values means over ends.